ANALISIS MINAT BERWIRAUSAHA MAHASISWA UNIVERSITAS PALANGKA RAYA - Oktaria, Merisa; agustini, Mega; Hariansano, Hendry Wahyu; Setyanto, Zola Ari; Holga, Holga (Universitas Dharmawangsa, 2024)
This research uses qualitative research. And using a comparative method, this research is aimed at looking at the differences in the entrepreneurial motivational interests of early stage business teams and P2MW growth stage business teams. The scope discussed in this research is the entrepreneurial interests of Palangka Raya University students. The objects of the author's research are all 19 students who received grants from the 2024 Student Entrepreneurship Development Program at Palangka Raya University. The research results show that the experience and basic knowledge of entrepreneurship that participants bring to the P2MW program influences the way they interact and utilize this program. And this influences students' entrepreneurial motivational interest. And it is hoped that future researchers will be able to delve more deeply into the topic being researched and have as many informants as possible.